2011
DOI: 10.1039/c0nr00635a
|View full text |Cite
|
Sign up to set email alerts
|

Sonochemical formation of metal sponges

Abstract: A novel sonochemical method for formation of mesoporous metal sponges is developed. Systematic investigation of ultrasound effects on various types of metal particles reveals the cavitation-induced oxidation of metal surface and etching of metal matrix as main factors in the ultrasound-driven metal modification. Beyond the specific examples, the findings provide guidelines for expansion of the concept towards a broad variety of metal systems and allow development of the sonochemical approaches to manipulation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
55
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

7
2

Authors

Journals

citations
Cited by 54 publications
(57 citation statements)
references
References 58 publications
2
55
0
Order By: Relevance
“…Recently, we demonstrated that ultrasonic treatment of biocompatible metal surfaces (aluminum, magnesium, iron, and titanium) changes their morphology (roughness, porosity), chemistry (surface oxidation by the products of water sonolysis) and properties (adhesion, hydrophilic/hydrophobic etc). [17,24] Intensive etching and oxidation of metals by ultrasound leads to formation of a 200-nm-thick sponge-like surface layer well-adhered to the bulk metal. The surface metal sponge is porous, has a high surface area and is covered by active OH-groups.…”
Section: Doi: 101002/adma201103786mentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, we demonstrated that ultrasonic treatment of biocompatible metal surfaces (aluminum, magnesium, iron, and titanium) changes their morphology (roughness, porosity), chemistry (surface oxidation by the products of water sonolysis) and properties (adhesion, hydrophilic/hydrophobic etc). [17,24] Intensive etching and oxidation of metals by ultrasound leads to formation of a 200-nm-thick sponge-like surface layer well-adhered to the bulk metal. The surface metal sponge is porous, has a high surface area and is covered by active OH-groups.…”
Section: Doi: 101002/adma201103786mentioning
confidence: 99%
“…[26] Thus, cavitation stimulates intercalation of low molecular weight compounds into the porous interior of metal sponges. [27] We applied here this effect of sonication to incorporate the antiseptic/ disinfectant, silver (Ag), into a porous Al surface. The ultrasonic assisted generation of surface Al sponges and their upload with Ag was performed in a step-wise mode at the same reactor unit (Figure 1).…”
Section: Doi: 101002/adma201103786mentioning
confidence: 99%
“…Moreover, active OH-groups formed during the preparation procedure allow for an effective encapsulation of relevant bioactive molecules and formation of sponge-like structures. [41,42] We have recently reported on the response of C2C12 mouse myoblast precursor cells, including their differentiation behavior, to mesoporous titania and titania nanotubes. [43] Titania nanotubes are a well-studied material, [44] produced by anodic oxidation which leads to the formation of TiO 2 nanotube arrays.…”
Section: Introductionmentioning
confidence: 99%
“…The focus is on formation of a nanofoam layer. In water Ti exhibits minor nanofoam layer formation after 60 min of sonication [30]. Ti has a high melting point, and the physical effect of melting is prevalent over other effects of ultrasonic irradiation, therefore one can observe a slight increase in surface roughness.…”
Section: Resultsmentioning
confidence: 99%